The Effect of Company Size and Funding Policy on Profitability in the Property Industry on the Indonesia Stock Exchange - Herna Deswarti; Freddy Herdian; Muhammad Akbar; Nuriatullah (Jurnal Ilmu Perbankan dan Keuangan Syariah, 2025)
This study aims to examine the effect of company size and funding policy on profitability in the property industry on the Indonesia Stock Exchange in 2011-2013. The data used is secondary data in the form of annual reports of the property industry listed on the Indonesia Stock Exchange. After passing the purposive sampling stage, the feasible sample used was 31 companies listed on the IDX. The results showed that the variables of Company Size and Funding Policy simultaneously had a positive and significant effect on Profitability. Partially, the variable Company Size has a positive and significant effect on Profitability. While Funding Policy has a negative and insignificant effect on Profitability. The results of this study are expected to be used as guidelines for investors in determining investment decision making in the property industry.